Reduced exposure of imatinib after coadministration with acetaminophen in mice - Nassar, Inthisham (Medknow Publications, 2009)
PURPOSE: Imatinib is an efficacious drug against chronic myeloid leukemia (CML) and gastrointestinal stromal tumor (GIST) due to selective inhibition of c-KIT and BCR-ABL kinases. It presents almost complete bioavailability, is eliminated via P450-mediated metabolism and is well tolerated. However, a few severe drug-drug interactions have been reported in cancer patients taking acetaminophen. MATERIALS AND METHODS: Male ICR mice were given 100 mg/kg single dose of imatinib orally or imatinib 100 mg/kg (orally) coadministered with acetaminophen intraperitoneally (700 mg/kg). Mice were euthanized at predetermined time points, blood samples collected, and imatinib plasma concentration measured by HPLC. RESULTS: Imatinib AUC(0-12) was 27.04 ± 0.38 mg·h/ml, C(max) was 7.21 ± 0.99 mg/ml and elimination half-life was 2.3 hours. Acetaminophen affected the imatinib disposition profile: AUC(0-12) and C(max) decreased 56% and 59%, respectively and a longer half-life was observed (5.6 hours). CONCLUSIONS: The study shows a pharmacokinetic interaction between acetaminophen and imatinib which may render further human studies necessary if both drugs are administered concurrently to cancer patients.